Determination of Quercetin in Iraqi Green Walnut Husk via Green Ionic Liquid-Based Digestion Extraction and Gel Filtration Procedures-Spectrophotometry and Microfluidic Paper-Based Analytical Platform Detection - Murtadha A. Mohammad; Jwan Oday Abdulsattar; Zaizafoon N. Nasif Nasif (مجلة بغداد للعلوم, 2024)
This study was conducted to extract, isolate and quantify Quercetin from Iraqi green walnut husk (GWH) using a novel ionic liquid-based digestion extraction and gel filtration procedure coupled with visible spectrophotometry detection and compared with a novel microfluidic paper-based analytical device (µPADs) aiming for an economic, and green method. 1-butyl-3-methylimidazolium chloride (BMIMCl) aqueous solution was used as a green solvent alternative to conventional organic solvents due to their impressive solvation properties.  The results showed that 100 mg of plant husk required 15 mL of BMIMCl solvent, and 30 minutes of digestion at 75° C, which involves a simpler, and greener extraction method compared with other extraction methods. Under optimal conditions, Quercetin was isolated using a gel filtration technique, and further investigations were conducted using high-performance liquid chromatography and Fourier-transmitted infrared to confirm the isolation of Quercetin. Aluminum chloride assay was selected to determine the concentration of Quercetin giving a linearity of  10-100 mg L-1 and correlation coefficient of 0.9369 and 0.7917 for spectrophotometric and µPADs methods, respectively. The antioxidant activity of isolated Quercetin showed good antioxidant activity and the ANOVA test was used to compare µPADs method with the spectrophotometric method and the results showed that there was no statistically significant difference between the two methods. In conclusion, BMIMCl solvent provides an excellent safe and suitable solvent for the extraction of phytochemicals from botanical drugs. In addition, the µPADs platform has been approved for its superiority against traditional methods for analytical purposes due to its green characteristic.